Changing the face of medicine in Canada with Dr. John Murray Last, Public Health Scholar and Emeritus Professor at the University of Ottawa - Gaeun Rhee; Tharshika Thangarasa (University of Ottawa Journal of Medicine, 2017)
Abstract